The influence of augmented reality (AR) technology on online purchase intention through customer experience as a mediating variable - Riviera Clarissa; Thomas Budhyawan Yudha (Universitas Nusa Cendana, 2026)
This study aims to examine the effect of augmented reality (AR) on online purchase intention, with customer experience as a mediating variable, in the context of beauty product shopping via e-commerce. The research was conducted on users who had experienced Shopee’s AR features, BeautyCam and SkinCam, through a quantitative method using PLS-SEM. The findings show that AR positively influences both customer experience and online purchase intention. Furthermore, customer experience significantly mediates the relationship between AR and online purchase intention. These results suggest that AR enhances the shopping experience by making it more interactive and immersive, which in turn strengthens customers’ intention to purchase. This study highlights the strategic value of AR in improving customer engagement and conversion, especially in the beauty sector. However, it is limited to a single e-commerce platform and product category. Future research may explore different contexts or compare multiple AR implementations across platforms. Keywords: Augmented Reality; Customer Experience; Online Purchase Intention; E-Commerce; Beauty Product